Truncated palladium nanocubes: Synthesis and the effect of OH− concentration on their catalysis of the alkaline oxygen reduction reaction. (1st March 2015) - Huang, Kun-Lung; Liu, Zhe-Ting; Lee, Chien-Liang
Graphical abstract: Highlights: A simple method for synthesizing truncated Pd nanocubes (14 nm) has been developed. The OH − concentration effect on Pd nanocubes for catalyzing ORR is studied. The ORR characteristics by Pd nanocubes and nanoparticles are compared. The ORR mechanisms on Pd nanocubes in 1-M and 0.1-M NaOH solution are proposed. Abstract: Small palladium nanocubes (14 nm) are successfully synthesized by increasing the amount of reducing agent (ascorbic acid) to improve the nucleation rate. From the results of X-ray diffraction and high-resolution transmission electron microscopy analyses, we conclude that the prepared nanocubes are truncated and contain (1 0 0) planes on six facets, with (1 1 1) planes appearing at the corners of the nanocubes. Additionally, these truncated nanocubes are used as catalysts for oxygen electroreduction and are compared with conventional Pd nanoparticles. Comparable cyclic voltammograms show that the Pd nanocube surface easily adsorbs OH − ions in a 1 M NaOH solution compared with surfaces in a 0.1 M NaOH solution. As demonstrated by the results of a rotating ring-disk electrode measurement, the associated Tafel slopes and specific activities in terms of the electrochemical surface area for these Pd nanocubes in both electrolytes show OH − concentration-independent characteristics. Furthermore, at 0.9 V (vs. RHE) in the 0.1 M NaOH solution, the specific activity of the 14 nm Pd nanocubes is 0.52 mA cm −2, superior to the value of 0.26 mA cm −2 for Pd nanoparticles.